1995
DOI: 10.1002/gps.930100607
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and phenomenology of psychotic symptoms in dementia sufferers

Abstract: SUMMARYOne hundred patients referred to old age psychiatry services in the West Midlands and 25 patients referred to a memory clinic in Bristol with mild to moderate dementia were assessed using the GMSMAS schedule together with a detailed inventory to assess their psychotic symptoms. On careful evaluation one patient did not have dementia. Eighty-three of the other 124 patients (66.9%) had at least one psychotic symptom. The prevalence of psychotic symptoms in the patients from the West Midlands and from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 31 publications
2
76
0
Order By: Relevance
“…Of those patients reporting visual hallucinations, a half will also have auditory and onequarter will have tactile hallucinations, although these are almost always at different times [10]. Multisensory hallucinations in which something can be seen, heard and felt are exceptionally rare.…”
Section: Recognizing Visual Hallucinations In Neurodegenerative Disormentioning
confidence: 99%
“…Of those patients reporting visual hallucinations, a half will also have auditory and onequarter will have tactile hallucinations, although these are almost always at different times [10]. Multisensory hallucinations in which something can be seen, heard and felt are exceptionally rare.…”
Section: Recognizing Visual Hallucinations In Neurodegenerative Disormentioning
confidence: 99%
“…Psychosis in AD is represented by the occurrence of delusions or hallucinations that have their onset after the appearance of the dementia, are present for at least 1 month, are severe enough to disrupt patient function, and do not occur during a delirium [36]. The prevalence of delusions in cross-sectional studies ranges from 40 to 65% and of hallucinations from 10 to 20% [37,38]. Frequent delusions in AD involve fear of theft, persecution, infidelity and misidentification of family members and home locations.…”
Section: Nps In Admentioning
confidence: 99%
“…Some authors have shown that attention fluctuations play a fundamental role in these pathologies [10,11] , and both attentional and perceptual processing might underlie the visual hallucinations that are experienced by most DLB patients. For instance, Calderon et al [6] showed that DLB patients performed poorly and below AD patients in most visuoperceptual tasks that required both the ventral and the dorsal processing pathways, and in all attentional tasks that needed sustained, selective and divided attention.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, AD patients were impaired in tasks that required the ventral processing pathway, but showed uncompromised sustained attention compared with the matched control group. Ballard et al [10] assessed attention performance through the use of a standardized battery of computerized tasks that required both rapid and accurate responses. DLB patients were impaired in both cognitive reaction time (RT) and the vigilance tasks compared with AD patients, and likewise exhibited greater variability in RTs.…”
Section: Introductionmentioning
confidence: 99%